Sistemas de gerenciamento na nova economia - Loureiro, Guilherme Macedo de Souza (2002)
Globalization, desregulation, tecnology development and other recent changes in the world have definetively changed the way value is created and businesses are managed. In this new era, called the new economy or the knowledge economy, it is much more important to concentrate efforts on intangible assets than on tangible ones, since the intangibles constitute the factor that most contribute to the creation of wealth. From among the intangibles, the most important is knowledge. For the purpose of this work, knowledge is defined as the capacity of use and increase people' s intelligence in order to generate more intelligent and competitive products and companies. From among all the management and measurement tools that have been developed with the intention of helping to improve management of intangible assets and create shareholder value, the best known and most used are the Balanced Scorecard, the Navigator Skandia, and the Intangible Assets Monitor. These models recognize that it is important to use both financial and non-financial measures. Traditional financial measures are lagging indicators, showing only the consequences of what has been done in the past. Despite the fact that these models are a great advance towards a management system for the new economy, they have not yet been concluded. Additional work needs to be done in order to correct some of their shortfalls. The model proposed in this work addresses these issues. It concentrates on the performance drivers and its main objective is to facilitate management actions in implementing a strategy aimed at maximizing the value of the business. The main assumptions upon which. the model is based are: each company's strategy should be unique, consequently the management framework should be unique; the starting point of any model should be the strategic intent of the company rather than the standard perspectives of a management tool; once the strategy is agreed, it is necessary to define which conditions are necessary to deliver it; such conditions will demand a series of actions that, once completed, will create the necessary conditions; the identification of these actions or performance drivers makes management more effective; since intangible assets are the most important value creation drivers, the majority of those actions should be related to them; the actions chosen need to be prioritized based on their importance in achieving the conditions; there are no predefined actions or focus areas, as everything depends on the strategy chosen. The case study was chosen as the most appropriate metodology for validating the proposed model was validated via the analysis of management systems in two companies.